Optimization of Carbonization Temperature in the Production of Coconut Pulp-Based Activated Carbon for Thermoelectric Materials - Nabila, Aliya; Darvina, Yenni; Gusnedi, -; Hidayat, Rahmat (Department of Physics – Universitas Negeri Padang UNP, 2024)
A thermoelectric generator is one of the power plants capable of converting thermal energy into electrical energy. Thermoelectricity can be derived from materials based on metal oxide composites with carbon materials, one example is the use of Copper (II) Oxide with activated carbon. Using activated carbon can help reduce thermal conductivity, which will be beneficial in its utilization as a thermoelectric material. Activated carbon comes from biomass waste that has not been fully utilized, such as coconut pulp waste. Utilization of coconut pulp waste can reduce environmental pollution and can add economic value to the waste. The goal of this research is to produce coconut pulp activated carbon at the ideal temperature for usage as thermoelectric materials. The research method used is the experimental method. Coconut pulp activated carbon is obtained through dehydration, carbonization and activation stages. The carbonization temperature variation used is at a temperature of 250ºC, 300ºC, 350ºC, 400ºC, and 450ºC. According to the results of the characterization, the yield, ash content, and bound carbon content of activated carbon decrease with increasing carbonization temperature, while the values of water content and ash content of activated carbon increase. This indicates that the activated carbon made from coconut pulp has met the requirements SNI 06-3730-1995. XRD characterization results show that coconut pulp activated carbon is amorphous and does not show sharp diffraction peaks (significant). For producing activated carbon, coconut pulp is carbonized at a temperature of 300oC to get the optimum temperature.